Growth and natural content of the red seaweed, Gracilaria bailinae (Zhang et el., 1995) growth under different feritilization scheme. - Almojuela, Kristine Marie
The accelerated development of fish aquaculture has caused many environmental problems. The most eveident effects resulting from this activity is the increase in organic material, the reduction in dissolved oxygen and the excessive rise in inorganic nutrients such as nitrogen, phosphorus and carbon dioxide. The integration of seaweeds to fed cultured species has long been organized as promising approach to reduce the excess nutrients released by aquaculture activity. The nitrogen and phosphate uptake kinetics, growth and nutritional content of the seaweed Gracilaria bailinae were studied in a series of outdoor tanks, fertilized with commercial fertilizer (NH4C1, NaNO3, and Na2HPO4) and shrimp culture waste water. The nutritional content of G. bailinae before and after fertilization was also determined through proximate analysis. Results showed a significant removal of dissolved nutrients by G. bailinae, although definite uptake rate could not be determined since the data were erratic and Michaelis-Menten model could not be applied. Seaweeds fertilized with shrimp waste water showed best specific growth rate (1.37+-0.2 percent d-1) over other fertilization scheme. This suggest that shrimp pond effluents could promote growth on G. bailinae. Local G. bailinae had high protein content per se (14 percent) but became more enhanced when fertilized with commercial or shrimp waste water (23-32 percent). In contrast, its carbohydrate content dropped when heavily fertilized from 39 percent to 19 percent.